(untitled) (Nordic Journal of African Studies, 2005)
There are different ways to look at the subject of socio-political corruption. One approach is to consider it as a moral depravity of persons and groups. In this case, addressing the problems of corruption consists in launching ‘wars against corruption’, which target individuals or groups of people. This essay considers corruption from another angel, namely, more as a structural problem. It argues that an uneven socio-political landscape, where necessary checks and balances scarcely exist and where the ordinary citizens are stripped of the power to demand accountability or call their rulers to order, is a breeding ground of corruption. It argues specifically that colonialism in Africa re-created social and political terrains and introduced a new unbalanced socio-political culture, which has given birth to the monster of uncontrollable corruption in African contemporary public service. Corruption in turn breeds poverty and poverty fortifies the practice of corruption, thus creating a vicious circle. This essay uses the socio-political transformation of the Igbo speaking people of Southern Nigeria, occasioned by colonialism, as a reference point. It argues that confronting corruption realistically would involve structural considerations, which would include fundamental changes in the perception of public office, creating the necessary checks and balances to enable the ordinary citizens exercise sufficient pressures on their public officials.